Effect of Using Probiotic (GUT PRO) on Growth Performance and Gut Morphology in Broiler - Sriboonyong, Pichet; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2019)
This study was conducted to investigate the effect of GUT PRO on growth performance and gut histology of broiler. One thousand, four hundred and forty day old Ross 308 were randomly allotted into 4 groups of 12 replications, each replication containing 30 birds. The experimental diets were divided into 4 groups as following T1: Control group (without supplemented GUT PRO), T2: Supplemented GUT PRO 0.5 ml/5.0 L in drinking water at 1-35 DOA, T3: Supplemented GUT PRO 1.0 ml/5.0 L in drinking water at 1-35 DOA and T2: Supplemented GUT PRO 1.0 ml/5.0 L in drinking water at 1-21 DOA. The trial was run between 1 and 35 days of age.Feed in crumbled pellet form and water were provided Ad-libitum throughout the experiment. The results revealed that feeding GUT PRO had no significant difference in body weight gain, feed intake, FCR and mortality rate among dietary treatments (P>0.05). The effect of feeding GUT PRO on gut histology shown that supplemented GUT PRO had no significant difference on gut morphology (P>0.05) in jejunum and ilium. Supplementation GUT PRO 1.0 ml/ 5 l of drinking water for 35 day of age increased villus height/crypt depth ratio in jejunum but had no significant difference in Ilium (P>0.05). The effect of feeding GUT PRO on intestinal bacterial counts and NH3 in excreta are shown that there was no significant difference in intestinal bacterial counts among dietary treatments (P>0.05). Feeding no probiotic in water had negative effect on ammonia content in excreta (P<0.05). Supplementation of probiotic in drinking water is an alternative way to supplement probiotic for broiler because supplementation probiotic in feed may destroyed in feed processing.